Antony, Cleopatra and the Uses of Mythology - Valentini, Maria (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2018)
This article discusses the uses of mythological allusions in Shakespeare’s Antony and Cleopatra whose eponymous protagonists seem at times to reenact such myths as those of Mars and Hercules, or of Venus and Isis, yet at other times to debunk them. The chosen myths, however, are controversial in themselves and enhance the well-known ambiguities of the main characters and the multiple perspectives of interpretation of the play as a whole. Keywords: Antony and Cleopatra, Plutarch, Hercules, Isis, Venus, Mars